Antioxidant Activity of Flavonoids from T. catappa Linn Fruit Flesh Fractionated using Continuous Column chromatography - Widyaningsih, Senny; Chasani, Moch.; Rastuti, Undri; Nurhandayani, Santi; Azahra, Silena; Pratiwi, Salma Yuni (Universitas Jenderal Soedirman, 2026)
ABSTRACT. Terminalia catappa L. is traditionally used as antioxidant anti-inflammatory, antimicrobial, hepatoprotector, vermifuge, anticancer and antidiabetic. Especially the flesh of T. catappa fruit has potential as an antioxidant. There has been no research that conducts a fractionation process using column chromatography to find antioxidant active fractions from fruit flesh of T. catappa. Therefore, this research aims to find the antioxidant active fraction of the fruit flesh T. catappa. The research steps began with the extraction process using methanol and continued with fractionation using n-hexane and ethyl acetate. The ethyl acetate fraction (with antioxidant activity IC50 = 246.3 ppm) was subjected to the first column chromatography with a gradient of increasingly polar eluents. The fractionation results obtained 4 subfractions with the highest antioxidant activity found in subfraction 3 (FG3) with IC50 = 81.9 ppm containing phenolic, flavonoids, and terpenoids compounds. FG3 was fractionated again using second column chromatography. The fractionation results obtained 2 subfractions with antioxidant activity IC50 = 76.936 ppm (FG1P) and 82.745 ppm (FG2P). FG1P contains phenolic secondary metabolites, namely flavonoids of the isoflavone class. The results provide information that the compounds acting as antioxidants in T. catappa fruit flesh are flavonoids presumably from the isoflavone class. The discovery of flavonoid compounds that act as antioxidants in T. catappa fruit flesh can be developed in the pharmaceutical industry. Keywords: Antioxidant, fruit flesh, Lisoflavone, T. catappa